Gabon : Fourth Review Under the Stand-By Arrangement and Review of Financing Assurances. (IMF Staff Country Reports; Country Report, 2005)
This paper discusses key findings of the Fourth Review Under the Stand-By Arrangement and Review of Financing Assurances for Gabon. Rising non-oil revenue and continued expenditure control contributed to maintaining fiscal discipline, and all quantitative performance criteria for end-March 2005 were observed. Structural fiscal reforms are needed to improve the quality of public spending. Public expenditure management needs to be strengthened by improving both budget preparation and budget execution. The Gabonese authorities have expressed a desire to remain closely engaged with the IMF through a multiyear follow-up arrangement.